EFEKTIVITAS TERAPI MUSIK MOZART PADA PENURUNAN TINGKAT STRES TERHADAP PENDERITA KANKER PAYUDARA YANG MENJALANI KEMOTERAPI DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2024 - Syahri, Alfi; rosaulina, meta; gurusinga, mona fitri (Jurnal Penelitian Keperawatan Medik, 2024)
Cancer is a worldwide health issue. Many breast cancer patients are treated with chemotherapy, which causes them to experience stress. Stress has an impact on the immune system. Sufferers who are stressed are more likely to have bodily discomfort. Breast cancer patients receiving chemotherapy can benefit from music therapy. Music provides organized aural stimulation in the form of melody, rhythm, harmony, form, and style. This study employs quantitative research and a quasi-experimental research design with a one-group preset-posttest design technique. The data was evaluated using the paired sample test. There are 34 samples available that were collected utilizing the entire sampling method. Data was gathered using questionnaires and observation sheets. The bivariate analysis gave a p-value of 0.0080.05, indicating that the Effectiveness of Mozart Music Therapy on Reducing Stress Levels in Breast Cancer Patients Undergoing Chemotherapy at Sembiring Deli Tua Hospital in 2024 will be present.